Fully funded social security pensions, lifetime risk and income - Laps, Jochen (Discussion paper series, 2015)
The paper analyzes the welfare consequences of insuring mortality risk by means of standard, fully funded Social Security pensions when individuals wish to make transfers to their heirs. In the presence of uninsured mortality risk, within-family transfers depend on realized lifespan. While crowding out private transfers, Social Security provides transfer insurance and insurance of the ex ante risk of future generations inheriting a particular amount of transfer wealth. We find that, once ex ante insurance is taken into account, Social Security is welfare improving over the long-run as long as capital is not too productive and the transfer motive is not too strong. Altruists gain far less from Social Security than egoists.
Keywords: Arbeitspapier; Graue Literatur